Karakteristik Kimia dan Analisis Sensori Pada Dodol Nanas Dengan Perbandingan Tepung Ketan dan Tepung Beras - Radwitya, Erick; Nopriyanti, Marisa; Adimarta, Trian; Ernayani, Ely (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
Dodol made from pineapple fruit ingredients is likely to add to the diversity of dodol that already exists in the market. In addition, it can also increase the economic value of pineapple fruit. The goal to be achieved is to determine the influence of various differences in the addition of glutinous rice flour and rice flour on the chemical and organoleptic properties of pineapple dodol. This type of research is to use an experimental method using a list of fingerprint analysis. The process of making pineapple dodol is made with four variations of the ratio of ingredients, namely the first addition of glutinous rice flour 15 gr and rice flour 5 gr, the second addition of glutinous rice flour 5 gr and rice flour 15 gr, the third addition of glutinous rice flour 20 gr and the fourth addition of rice flour. 20 gr. The water content contained in the D treatment (rice flour 20%) has a higher water content of 33.86% this is due to the increasing concentration of rice flour, there is an increase in the water content of pineapple dodol. This is due to the addition of rice flour. because of the starch property that is to like water.